Isolated fallopian tubal torsion with underdiagnosed entity: a case report - Park, Seon Hee; Yun, Jisun; Chung, Eun (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Isolated fallopian tubal torsion refers to twisting only the tube without involving the ipsilateral ovary. This is a rare type of adenexal torsion and is a gynecological emergency. Since this disease mostly occurs in women of childbearing age, accurate diagnosis and appropriate treatment are more important issues. It is known that ovarian cyst torsion occurs well in sizes greater than 5 cm, but the epidemiology of isolated fallopian tubal torsion is unknown. Even clinically, in patients complaining of abdominal discomfort, a small andexal cyst is difficult to consider as a cause of pain. We presented an isolated fallopian tubal torsion case that can be twisted despite its small size.